2011
DOI: 10.1111/j.1750-3841.2011.02418.x
|View full text |Cite
|
Sign up to set email alerts
|

High Pressure Homogenization Increases the In Vitro Bioaccessibility of α‐ and β‐Carotene in Carrot Emulsions But Not of Lycopene in Tomato Emulsions

Abstract: A better understanding of the correlation between the processing of fruits and vegetables, microstructure and nutrient bioaccessibility can be directly applied in the production of food products with an increased nutritional value.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
49
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(56 citation statements)
references
References 51 publications
(66 reference statements)
7
49
0
Order By: Relevance
“…Regarding vegetable and fruit, a correlation between food microstructure and in vitro bioaccessibility of antioxidant components as carotenes as been already reported [25].…”
Section: Open Access Fnsmentioning
confidence: 98%
“…Regarding vegetable and fruit, a correlation between food microstructure and in vitro bioaccessibility of antioxidant components as carotenes as been already reported [25].…”
Section: Open Access Fnsmentioning
confidence: 98%
“…The processing factors (food texture, e.g., heat, temperature, or pressure application) can impinge on the bioaccessibility (fraction of a compound that is released from the matrix and potentially available for further uptake and absorption) of bioactivity [168]. The elimination of a natural barrier of the cell wall yields a better release of phytocompounds.…”
Section: Phytochemicals Bioavailability and Their Effect On Human mentioning
confidence: 99%
“…For example, different studies reported the effect of HPH on several properties of tomato products, including changes in the consistency. [10,[18][19][20][21][22] On the other hand, the MP-HPH was not effective for further changing the rheological properties of tomato juice [23] , where only the first process showed eligible effects. Then, the aim of this study was to evaluate the use of multiple passes of high-pressure homogenisation (MP-HPH) on FCOJ below the upper limit, in order to evaluate if a number of processes under mild conditions could be compared with one process at 150 MPa.…”
Section: Introductionmentioning
confidence: 99%